(untitled) (Global Journal of Management and Business Research, 2025)
Abstract- The objective of this research is to understand how cultural diversity management contributes to the social performance of Cameroonian SMEs To achieve this objective we used a qualitative approach The semi-directed interviews conducted with SMEs in the city of Yaound made it possible to collect data that were analyzed using Nvivo10 software The results show that good cultural diversity management contributes to improving the social climate and working conditions in particular through a number of factors such as internal regulations and procedures manuals organizational culture flexible informal management training and staff awareness To this end we recommend that SMEs implement less rigid organizational systems for better inclusive participation of employees in the company in order to ensure transparent internal communication